Functionally relevant white matter degradation in multiple sclerosis: a tract-based spatial meta-analysis - Welton, Thomas; Kent, Daniel; Constantinescu, Cris S.; Auer, Dorothee P.; Dineen, Robert A. (Radiological Society of North America, 2015)
Purpose